Nickel-cobalt-manganese-aluminum precursor with two-phase structure as well as preparation method and application of nickel-cobalt-manganese-aluminum precursor

By adopting a nickel-cobalt manganese-aluminum precursor with a two-phase structure, using nickel-cobalt manganese hydroxide and Al(OH)3 secondary particles, the problems of flocculation precipitation of Al(OH)3 and the formation of poor phases of Al elements in the prior art are solved, and the high tap density and electrochemical performance of nickel-cobalt manganese aluminate quaternary material are improved.

CN119542411APending Publication Date: 2025-02-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311110502.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing synthesis process of nickel-cobalt-manganese-aluminate quaternary materials has Al(OH)3 floc precipitation problem, resulting in poor spherical shape, small particle size, loose structure, and low tap density. In addition, Al elements are prone to generate γ-LiAlO2 or β-LiAlO2 phases during the lithiation and roasting process, resulting in poor batch stability of the material and unstable discharge specific capacity.

Method used

A nickel-cobalt-manganese-aluminum precursor with a two-phase structure, which includes secondary particles containing nickel-cobalt-manganese hydroxide and Al(OH)3. The material containing nickel-cobalt-manganese-aluminum nanoparticles is used under stirring conditions, and lithium nickel-cobalt-manganese aluminum lithium aluminum material with high tap density and good electrochemical properties is formed.

Benefits of technology

The tap density and electrochemical performance of the nickel-cobalt-manganese-aluminate quaternary material are improved, the batch stability of the material is enhanced, and the difficulty of process control is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention relates to a nickel-cobalt-manganese-aluminum precursor with a two-phase structure as well as a preparation method and application of the nickel-cobalt-manganese-aluminum precursor. The nickel-cobalt-manganese-aluminum precursor comprises secondary particles containing nickel-cobalt-manganese hydroxide and Al (OH) 3. The nickel-cobalt-manganese-aluminum precursor prepared by the method disclosed by the invention is relatively large in particle size and high in tap density, the tap density and the electrochemical performance can be improved by using the nickel-cobalt-manganese-aluminum precursor to prepare the lithium nickel-cobalt-manganese-aluminate quaternary material, and the batch stability of the material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of lithium-ion battery positive electrode material precursors, and in particular to a nickel-cobalt-manganese-aluminum precursor with a two-phase structure, and a preparation method and application thereof. Background Art

[0002] Nickel cobalt manganese aluminum oxide (NCMA) has the advantages of high energy density, long cycle life and good safety performance, and has been widely used in the field of power batteries for electric vehicles. Nickel cobalt manganese aluminum hydroxide quaternary precursor is the key raw material for the preparation of NCMA quaternary materials. At present, the synthesis of NCMA mainly includes two process routes.

[0003] One process route is to first directly prepare the nickel-cobalt-manganese-aluminum hydroxide precursor by coprecipitation, and then mix it with lithium salt and calcine it to obtain NCMA material. -33 , while Ni(OH)2, Co(OH)2 and Mn(OH)2 are 2×10 -15 , 1.6×10 -15 and 4×10 -14 In addition, Al 3+ It is difficult to react with NH3 to form a complex. Therefore, when the nickel-cobalt-manganese-aluminum hydroxide precursor is prepared by conventional chemical precipitation, Al 3+ The precipitation speed is extremely fast, and flocculent precipitation is easily formed, resulting in poor sphericity, small particle size, loose structure and low tap density of the prepared precursor; and Al(OH)3 is an amphoteric hydroxide, and the control accuracy of pH value during the reaction is very high, and the synthesis technology is difficult.

[0004] Another process route is to prepare a nickel-cobalt-manganese hydroxide precursor by coprecipitation, and then mix it with aluminum oxide or hydroxide and lithium salt and calcine it to obtain a nickel-cobalt-manganese-aluminum lithium quaternary material. The advantage of this process is that the precursor synthesis is easy and it is easy to synthesize NCMA quaternary materials with large particle size and high tap density. However, since Al2O3 or Al(OH)3 easily produces γ-LiAlO2 or β-LiAlO2 phases during the lithiation calcination process, it is difficult to dope part of the Al into the main crystal structure, resulting in poor batch stability and unstable discharge capacity of the prepared NCMA material.

[0005] Chinese invention patent 201911045197.X discloses an aluminum-doped nickel-cobalt-manganese ternary positive electrode material precursor and its preparation method and application. The synthesis method of the patent is as follows: Step 1, prepare a mixed salt solution containing nickel ions, cobalt ions and manganese ions; Step 2, prepare an aluminum salt solution; Step 3, add the mixed salt solution in step 1, the aluminum salt solution in step 2, the sodium hydroxide solution and ammonia water to a reactor containing a bottom liquid in a parallel flow manner for coprecipitation reaction, and at the same time, introduce a protective gas into the reactor to obtain an aluminum-doped nickel-cobalt-manganese ternary positive electrode material precursor. The aluminum salt solution used in the patent is a sodium aluminate solution. The nickel-cobalt-manganese-aluminum precursor prepared by the patent method has a low tap density, which ultimately affects the energy density of the battery. Summary of the invention

[0006] The purpose of the present disclosure is to provide a nickel-cobalt-manganese-aluminum precursor and a preparation method and application thereof. The nickel-cobalt-manganese-aluminum precursor has a large particle size and a high tap density. Using it to prepare nickel-cobalt-manganese-aluminum lithium quaternary material can improve the tap density and electrochemical performance, and can improve the batch stability of the material.

[0007] In order to achieve the above objectives, the present disclosure provides, in a first aspect, a nickel-cobalt-manganese-aluminum precursor having a two-phase structure, wherein the nickel-cobalt-manganese-aluminum precursor comprises secondary particles containing nickel-cobalt-manganese hydroxide and Al(OH) 3 .

[0008] Optionally, the nickel-cobalt-manganese hydroxide has a β crystal form;

[0009] The chemical formula of the nickel-cobalt-manganese hydroxide is Ni 1-x-y Co x Mn y (OH)2, 0.05≤x≤0.15, 0.05≤y≤0.15.

[0010] Optionally, in the XRD spectrum of the nickel-cobalt-manganese-aluminum precursor, there are characteristic peaks of Al(OH)3 crystals and characteristic peaks of nickel-cobalt-manganese hydroxide crystals.

[0011] Optionally, the secondary particles have a two-phase microscopic crystal structure in which Al(OH) 3 crystals are dispersed in nickel-cobalt-manganese hydroxide crystals.

[0012] Optionally, the tap density of the secondary particles is 2.0 g / cm 3 Above, the specific surface area is 10-15m 2 / g, D50 is 8-15μm.

[0013] Optionally, in the nickel-cobalt-manganese-aluminum precursor, the molar ratio of aluminum element to metal element is (0.02-0.05):1.

[0014] The second aspect of the present disclosure provides a method for preparing a nickel-cobalt-manganese-aluminum precursor having a two-phase structure, the method comprising: under stirring, a first material containing a nickel source, a cobalt source, a manganese source and Al(OH)3 nanoparticles, a first alkaline solution and an ammonia solution are subjected to a first contact reaction and a second contact reaction, wherein the first contact reaction and the second contact reaction are carried out in an inert atmosphere;

[0015] The D50 of the Al(OH)3 nanoparticles is 10-50nm;

[0016] The first contact reaction is carried out under the condition that the pH value measured at a liquid temperature of 50° C. is 11.5-12.5;

[0017] The second contact reaction is carried out under the condition that the pH value measured at a liquid temperature of 50° C. is 10.0-10.6.

[0018] Optionally, the method for preparing the first material comprises: mixing a suspension containing the Al(OH)3 nanoparticles with a solution containing the nickel source, the cobalt source and the manganese source under stirring;

[0019] Optionally, the solid content of the suspension is 10-30% by weight;

[0020] Optionally, the total concentration of cobalt ions, nickel ions and manganese ions in the solution is 1.5-2.5 mol / L;

[0021] Optionally, in the first material, the molar ratio of aluminum element to metal element is (0.02-0.05):1.

[0022] Optionally, the nickel source includes nickel sulfate and / or nickel chloride;

[0023] The cobalt source includes cobalt sulfate and / or cobalt chloride;

[0024] The manganese source includes manganese sulfate and / or manganese chloride.

[0025] Optionally, the first alkaline solution contains sodium hydroxide and / or potassium hydroxide;

[0026] The concentration of the first alkaline solution is 4-10 mol / L, and the mass fraction of the ammonia solution is 15-22%.

[0027] Optionally, the method comprises the following steps:

[0028] a. Add water, the first part of the first alkaline solution and the first part of the ammonia solution into a reaction kettle under stirring;

[0029] The total volume of the water, the first alkaline solution of the first part and the ammonia solution of the first part accounts for 30-80% of the volume fraction of the reactor;

[0030] b. adding a portion of the first material, a second portion of the first alkali solution and a second portion of the ammonia solution into the reactor of step a under stirring to carry out the first contact reaction;

[0031] c. Under stirring conditions, adding another portion of the first material, the third portion of the first alkali solution and the third portion of the ammonia solution to the reactor in step b to carry out the second contact reaction, and stopping feeding when the D50 of the material in the reactor is 8-15 μm;

[0032] The first contact reaction time is 1-3 hours, and the second contact reaction time is 180-250 hours;

[0033] When the volume of the solid material in the reactor accounts for 80%-85% of the total volume of the reactor, the clear liquid is discharged from the reactor through a concentrator;

[0034] The inert atmosphere includes nitrogen atmosphere and / or argon atmosphere;

[0035] In step b and step c, the oxygen content in the reaction kettle is below 0.2 volume %.

[0036] Optionally, in step a, in the solution in the reactor, the concentration of NH3 is 3-10 g / L, the pH value of the solution in the reactor measured at a liquid temperature of 50° C. is 11.5-12.5, and the stirring power density of the solution is 7-9 W / L;

[0037] In step b and step c, the concentration of NH3 in the slurry in the reactor is 3-10 g / L, and the stirring power density of the slurry is 7-9 W / L;

[0038] The temperatures of the first contact reaction and the second contact reaction are 50-65° C., respectively.

[0039] Optionally, the method further comprises: performing alkaline washing on the second material obtained by the second contact reaction, wherein the alkaline washing comprises: washing the second material with water, a second alkaline solution and water in sequence until the pH value of the washing solution is below 8.0;

[0040] The second alkaline solution contains sodium hydroxide and / or potassium hydroxide, the concentration of the second alkaline solution is 1-2% by weight, and the alkaline washing time is 1-3 hours;

[0041] Optionally, the method further comprises: drying the third material obtained by the alkali washing, and the conditions of the drying treatment include: time of 3-8 hours and temperature of 120-200°C.

[0042] The third aspect of the present disclosure provides a nickel-cobalt-manganese-aluminum precursor having a two-phase structure prepared by the method described in the second aspect of the present disclosure.

[0043] A fourth aspect of the present disclosure provides a method for preparing a nickel-cobalt-manganese-aluminum lithium quaternary material, the method comprising:

[0044] The nickel-cobalt-manganese-aluminum precursor described in the first aspect or the third aspect of the present disclosure is mixed with a lithium source and then heat-treated in an oxygen-containing atmosphere.

[0045] Optionally, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium oxalate and lithium nitrate;

[0046] The molar ratio of the lithium source calculated as lithium element to the nickel-cobalt-manganese-aluminum precursor calculated as metal element is (1.03-1.06):1;

[0047] Optionally, the mixing method is solid phase ball milling, and the solid phase ball milling time is 1-5 hours.

[0048] Optionally, the heat treatment conditions include: time of 8-20h and temperature of 700-950°C.

[0049] The fifth aspect of the present disclosure provides a nickel-cobalt-manganese-aluminum lithium quaternary material prepared by the method described in the fourth aspect of the present disclosure.

[0050] Optionally, the tap density of the nickel-cobalt-manganese-aluminum-lithium quaternary material is 2.3 g / cm 3 Above, D50 is 8-15μm.

[0051] A sixth aspect of the present disclosure provides a lithium-ion battery, comprising a positive electrode, an electrolyte and a negative electrode, wherein the positive electrode comprises the lithium nickel-cobalt-manganese-aluminum oxide quaternary material described in the fifth aspect of the present disclosure.

[0052] Through the above technical scheme, the present invention mixes Al(OH)3 nanoparticles with a specific particle size with a solution containing a nickel source, a cobalt source and a manganese source, and precipitates under specific pH conditions to form a nickel-cobalt-manganese-aluminum precursor with a two-phase structure. The method of the present invention overcomes the technical difficulties that when the conventional liquid phase method is used to directly precipitate and synthesize nickel-cobalt-manganese-aluminum hydroxide, aluminum hydroxide flocculent precipitate is produced, resulting in the inability to increase the particle size and low tap density. The Al element in the nickel-cobalt-manganese-aluminum precursor of the present invention forms secondary spherical particles in the form of Al(OH)3 crystal phase and nickel-cobalt-manganese hydroxide crystal phase. The nickel-cobalt-manganese-aluminum precursor can be used as a precursor for synthesizing nickel-cobalt-manganese-aluminum lithium quaternary material positive electrode material. When the nickel-cobalt-manganese-aluminum precursor disclosed in the present invention is used to synthesize the nickel-cobalt-manganese-aluminum lithium oxide quaternary positive electrode material, the Al element can be prevented from generating γ-LiAlO2 or β-LiAlO2 phases, which causes the technical difficulty of making it difficult for some Al to be doped into the main crystal structure. The tap density and electrochemical properties of the NCMA quaternary material can be improved, and more importantly, the batch stability of the material can be improved. In addition, the synthesis method disclosed in the present invention has a wide pH value control range and is simple to operate, which reduces the control difficulty of industrial production.

[0053] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings:

[0055] Figure 1 This is the XRD pattern of the nickel-cobalt-manganese-aluminum precursor A1 prepared in Example 1 of the present disclosure.

[0056] Figure 2 This is the XRD diagram of the nickel-cobalt-manganese-aluminum precursor D1 prepared in Comparative Example 1 of the present disclosure.

[0057] Figure 3 This is a SEM image of the nickel-cobalt-manganese-aluminum precursor A1 prepared in Example 1 of the present disclosure.

[0058] Figure 4 This is a SEM image of the nickel-cobalt-manganese-aluminum precursor D1 prepared in Comparative Example 1 of the present disclosure.

[0059] Figure 5 This is the particle size distribution diagram of the nickel-cobalt-manganese-aluminum precursor A1 prepared in Example 1 of the present disclosure.

[0060] Figure 6 XRD curve diagrams of the nickel-cobalt-manganese-aluminum lithium quaternary materials A1-1, D1-1 and D2-1 prepared in Preparation Example 1, Preparation Comparative Example 1 and Preparation Comparative Example 2 of the present disclosure. DETAILED DESCRIPTION

[0061] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0062] In a first aspect, the present disclosure provides a nickel-cobalt-manganese-aluminum precursor having a two-phase structure, wherein the nickel-cobalt-manganese-aluminum precursor includes secondary particles containing nickel-cobalt-manganese hydroxide and Al(OH) 3 .

[0063] According to one embodiment of the present disclosure, in the XRD spectrum of the nickel-cobalt-manganese-aluminum precursor with a two-phase structure, there are characteristic peaks of Al(OH)3 crystals and characteristic peaks of nickel-cobalt-manganese hydroxide crystals; further, the secondary particles have a two-phase microstructure in which Al(OH)3 crystals are dispersed in nickel-cobalt-manganese hydroxide crystals; according to the above characteristics, it can be known that the nickel-cobalt-manganese-aluminum precursor of the present disclosure has a two-phase microscopic crystal structure, namely, it includes a crystalline phase of nickel-cobalt-manganese hydroxide and a crystalline phase of Al(OH)3, and the above two primary particles form secondary particles, and the above secondary particles can, for example, have a spherical and / or quasi-spherical shape, and the meanings of spherical, quasi-spherical and secondary particles are known in the art; the nickel-cobalt-manganese-aluminum precursor with a two-phase structure disclosed in the present disclosure has a large particle size and a high tap density, which can improve the tap density and electrochemical properties of nickel-cobalt-manganese-aluminum lithium positive electrode material (NCMA), and can improve the batch stability of the material.

[0064] According to one embodiment of the present disclosure, the nickel-cobalt-manganese hydroxide has a β crystal form, which can be tested by XRD; the chemical formula of the nickel-cobalt-manganese hydroxide is Ni 1-x-y Co x Mn y (OH)2, 0.05≤x≤0.15, 0.05≤y≤0.15.

[0065] According to one embodiment of the present disclosure, the tap density of the secondary particles is 2.0 g / cm 3 Above, D50 is 8-15μm, specific surface area is 10-15m 2 / g. The nickel-cobalt-manganese-aluminum precursor having the above structural characteristics can improve the tap density and electrochemical performance of NCMA when preparing NCMA.

[0066] According to one embodiment of the present disclosure, in the nickel-cobalt-manganese-aluminum precursor, the molar ratio of aluminum element to metal element is (0.02-0.05):1.

[0067] The second aspect of the present disclosure provides a method for preparing a nickel-cobalt-manganese-aluminum precursor having a two-phase structure, the method comprising: under stirring, a first material containing a nickel source, a cobalt source, a manganese source and Al(OH)3 nanoparticles, a first alkaline solution and an ammonia solution are subjected to a first contact reaction and a second contact reaction, wherein the first contact reaction and the second contact reaction are carried out in an inert atmosphere;

[0068] The D50 of the Al(OH)3 nanoparticles is 10-50nm;

[0069] The first contact reaction is carried out under the condition that the pH value measured at a liquid temperature of 50° C. is 11.5-12.5;

[0070] The second contact reaction is carried out under the condition that the pH value measured at a liquid temperature of 50° C. is 10.0-10.6.

[0071] On the one hand, the method disclosed in the present invention overcomes the technical difficulty that aluminum hydroxide flocculent precipitate is produced when directly precipitating and synthesizing nickel-cobalt-manganese-aluminum hydroxide by conventional liquid phase method, resulting in the inability to grow the particle size and low tap density; on the other hand, it also overcomes the technical difficulty that when a nickel-cobalt-manganese hydroxide precursor is first synthesized and then mixed with aluminum oxide or hydroxide and lithium salt and then calcined to prepare nickel-cobalt-manganese-aluminum lithium oxide quaternary material, the Al element generates γ-LiAlO2 or β-LiAlO2 phase, making it difficult to dope part of Al into the main crystal structure.

[0072] In the present disclosure, "pH value measured at a liquid temperature of 50° C." refers to a pH value measured at a temperature of 50° C. and a standard atmospheric pressure.

[0073] According to one embodiment of the present disclosure, the method for preparing the first material includes: mixing a suspension containing the Al(OH)3 nanoparticles with a solution containing the nickel source, the cobalt source and the manganese source under stirring; the method for preparing a suspension containing Al(OH)3 nanoparticles may, for example, include: mixing Al(OH)3 with water, and sand-milling the resulting mixture to form a suspension containing Al(OH)3 nanoparticles, the sand-milling time is 2-5h, the sand-milling speed is 2500-3000r / min, and the prepared suspension is always in a stirring state to prevent Al(OH)3 from precipitating to the bottom of the container; the solid content of the suspension is 10-30% by weight.

[0074] According to one embodiment of the present disclosure, the total concentration of cobalt ions, nickel ions and manganese ions in the solution is 1.5-2.5 mol / L, and the amount of cobalt source, nickel source and manganese source is set according to the ratio of Co, Ni and Mn in the desired product.

[0075] According to one embodiment of the present disclosure, in the first material, the molar ratio of aluminum element to metal element is (0.02-0.05):1.

[0076] According to one embodiment of the present disclosure, the types of nickel source and cobalt source are conventional in the art. The nickel source may be, for example, a soluble salt of nickel, the cobalt source may be, for example, a soluble salt of cobalt, and the manganese source may be, for example, a soluble salt of manganese; specifically, the nickel source includes nickel sulfate and / or nickel chloride; the cobalt source includes cobalt sulfate and / or cobalt chloride; the manganese source includes manganese sulfate and / or manganese chloride. When the cobalt source, the nickel source or the manganese source includes more than two substances, the present disclosure does not specifically limit their ratio.

[0077] According to one embodiment of the present disclosure, the first alkaline solution contains sodium hydroxide and / or potassium hydroxide, and the concentration of the first alkaline solution is 4-10 mol / L.

[0078] According to one embodiment of the present disclosure, the mass fraction of the ammonia solution is 15-22%.

[0079] According to one embodiment of the present disclosure, the method comprises the following steps:

[0080] a. Add water, the first part of the first alkaline solution and the first part of the ammonia solution into a reaction kettle under stirring;

[0081] The total volume of the water, the first alkaline solution of the first part and the ammonia solution of the first part accounts for 30-80% of the volume fraction of the reactor;

[0082] b. adding a portion of the first material, a second portion of the first alkali solution and a second portion of the ammonia solution into the reactor of step a under stirring to carry out the first contact reaction;

[0083] c. Under stirring conditions, adding another portion of the first material, a third portion of the first alkali solution and a third portion of the ammonia solution to the reactor in step b to carry out the second contact reaction, and stopping feeding when the D50 of the solid material in the reactor is 8-15 μm;

[0084] The first contact reaction time is 1-3 hours, and the second contact reaction time is 180-250 hours;

[0085] When the volume of the material in the reactor accounts for 80%-85% of the total volume of the reactor, the clear liquid is discharged from the reactor through a concentrator;

[0086] The inert atmosphere includes nitrogen atmosphere and / or argon atmosphere;

[0087] In step b and step c, the oxygen content in the reaction kettle is below 0.2 volume %.

[0088] According to one embodiment of the present disclosure, in step a, in the solution in the reactor, the concentration of NH3 is 3-10 g / L, the pH value of the solution in the reactor measured based on a liquid temperature of 50°C is 11.5-12.5, and the stirring power density of the solution is 7-9 W / L.

[0089] According to one embodiment of the present disclosure, in step b and step c, the concentration of NH3 in the slurry in the reactor is 3-10 g / L, and the stirring power density of the slurry is 7-9 W / L.

[0090] In the present disclosure, in step b and step c, the pH value of the solution or slurry in the reactor is controlled by controlling the addition rate of the first alkaline solution, and the concentration of NH3 is controlled by the introduction rate of the ammonia solution.

[0091] In the present disclosure, the pH values ​​of step a and step b are the same or different, preferably the same.

[0092] According to one embodiment of the present disclosure, after the first contact reaction is completed, the addition of the first alkaline solution is stopped, and after the pH value of the material in the reactor drops to the pH value of the second contact reaction, the first alkaline solution is continued to be introduced to carry out the second contact reaction.

[0093] According to an embodiment of the present disclosure, the temperatures of the first contact reaction and the second contact reaction are 50-65° C. respectively, wherein the time of the first contact reaction and the time of the second contact reaction are both the time of introducing the material.

[0094] In the present disclosure, the adding speed of the first material in step b and step c is conventional in the art.

[0095] According to one embodiment of the present disclosure, in order to further remove anions such as sulfate and chloride ions in the product, the method further includes: performing alkaline washing on the second material obtained by the second contact reaction, and the steps and conditions of the alkaline washing are conventional in the art, and may include: washing the second material with water, a second alkaline solution and water in sequence until the pH value of the washing liquid is below 8.0 (test value under normal pressure at 25°C); the second alkaline solution contains sodium hydroxide and / or potassium hydroxide, the concentration of the second alkaline solution is 1-2% by weight, and the total time of the alkaline washing is 1-3h.

[0096] According to an embodiment of the present disclosure, the method further comprises: drying the third material obtained by the alkali washing, and the conditions of the drying treatment comprise: a time of 3-8 hours and a temperature of 120-200°C.

[0097] The third aspect of the present disclosure provides a nickel-cobalt-manganese-aluminum precursor having a two-phase structure prepared by the method described in the second aspect of the present disclosure.

[0098] The nickel-cobalt-manganese-aluminum precursor described in the third aspect of the present disclosure has the same characteristics as the nickel-cobalt-manganese-aluminum precursor described in the first aspect of the present disclosure, which will not be repeated here.

[0099] A fourth aspect of the present disclosure provides a method for preparing a nickel-cobalt-manganese-aluminum lithium quaternary material, the method comprising:

[0100] The nickel-cobalt-manganese-aluminum precursor described in the first aspect or the third aspect of the present disclosure is mixed with a lithium source and then heat-treated in an oxygen-containing atmosphere.

[0101] According to one embodiment of the present disclosure, the lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium oxalate and lithium nitrate; the molar ratio of the lithium source calculated as lithium element to the nickel-cobalt-manganese-aluminum precursor calculated as metal element is (1.03-1.06):1.

[0102] According to one embodiment of the present disclosure, the mixing method is solid phase ball milling, and the solid phase ball milling time is 1-5 hours.

[0103] According to one embodiment of the present disclosure, the heat treatment conditions include: a time of 8-20 hours and a temperature of 700-950°C.

[0104] The fifth aspect of the present disclosure provides a method for preparing a nickel-cobalt-manganese-aluminum lithium quaternary material using the method described in the fourth aspect of the present disclosure.

[0105] According to one embodiment of the present disclosure, the chemical formula of the nickel-cobalt-manganese-aluminum lithium quaternary material is Li 1+δ Ni 1-a-b- c Co a Mn b Al c O2, where 0.03≤δ≤0.06, 0.0475≤a≤0.147, 0.0475≤b≤0.147, 0.02≤c≤0.05.

[0106] According to one embodiment of the present disclosure, the tap density of the nickel-cobalt-manganese-aluminum-lithium quaternary material is 2.3 g / cm 3 Above, D50 is 8-15μm.

[0107] A sixth aspect of the present disclosure provides a lithium-ion battery, comprising a positive electrode, an electrolyte and a negative electrode, wherein the positive electrode comprises the lithium nickel-cobalt-manganese-aluminum oxide quaternary material described in the fifth aspect of the present disclosure.

[0108] In the present disclosure, the types of negative electrodes and electrolytes of lithium-ion batteries are conventional in the art, and no specific requirements are made herein, as long as the solutions of the present disclosure can be implemented.

[0109] The present invention will be described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form.

[0110] The raw materials used in the examples were all purchased from commercial sources and were of analytical grade unless otherwise specified.

[0111] XRD test conditions and instrument model: Equipment model: Japanese UItima-III XX-ray powder diffractometer. Test conditions: Cu target Kα light source, wavelength λ=0.154nm, scanning speed of 5° / min, scanning range 2θ of 10-80°, step length of 0.04°.

[0112] SEM test conditions and instrument model: Equipment model: FEIQuanta 400 scanning electron microscope; Test conditions: test voltage is 5kV.

[0113] The test method and instrument model of tap density: Equipment model: Dandong Better BT-300 tap density tester. Test conditions: sample 100g, amplitude 3mm, vibration frequency 300 times / min, test time 5min.

[0114] The particle size test instrument model: Mastersizer 2000 laser particle size distribution analyzer produced by Malvern. The test conditions are: particle refractive index 2.16, particle absorption rate 0.1, dispersant is deionized water, dispersant refractive index 1.330, shading degree 5%-10%, and analysis mode is general.

[0115] The molar ratio of aluminum element to metal element in the nickel-cobalt-manganese-aluminum precursor is the same as the feed ratio.

[0116] Example 1

[0117] The nickel-cobalt-manganese-aluminum precursor A1 was prepared by the following steps:

[0118] (1) Dissolve NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O in deionized water to prepare a mixture containing Ni 2+ 、Co 2+ and Mn 2+ of solution;

[0119] The total concentration of nickel ions, cobalt ions and manganese ions is 2.2 mol / L, among which n(Ni 2+ ):n(Co 2+ ):n(Mn 2+)=84.2:5.3:10.5 (molar ratio);

[0120] Add Al(OH)3 to deionized water, and grind it at a speed of 3000 r / min for 3 hours to form a suspension containing Al(OH)3 nanoparticles with a solid content of 5 weight %; mix the suspension containing Al(OH)3 nanoparticles with a solution containing a nickel source, a cobalt source and a manganese source to obtain a first material; the first material is always in a stirring state to avoid precipitation of Al(OH)3;

[0121] The D50 of Al(OH)3 nanoparticles in the suspension containing Al(OH)3 is 30nm;

[0122] The molar ratio of Al(OH)3 to the metal element is 0.05:1.

[0123] Adding sodium hydroxide into deionized water to prepare a first alkaline solution with a concentration of 5 mol / L;

[0124] Add 25% concentrated ammonia water into deionized water to prepare an 18% ammonia solution;

[0125] (2) adding 5 L of deionized water into a 10 L reactor, and adding the first part of the first alkaline solution and the first part of the ammonia solution into the reactor under stirring as a reaction base solution;

[0126] The pH value of the reaction base liquid was 12.0 (pH value measured based on a liquid temperature of 50°C), the concentration of NH3 was 6 g / L, and the stirring power density of the reaction base liquid was 9 W / L;

[0127] (3) In a nitrogen atmosphere (the oxygen content in the reactor is 0.1% by volume), under the conditions of a stirring power density of 9 W / L and a reaction temperature of 60°C, a portion of the first material, a second portion of the first alkali solution, and a second portion of the ammonia solution are added to the reactor in parallel to carry out a first contact reaction, wherein the addition rate of the first material is 0.28 L / h. In addition, the reaction pH is maintained at 12.0 (pH measured based on a liquid temperature of 50°C) by adjusting the addition rate of the first alkali solution, and the NH3 concentration is maintained at 6 g / L by adjusting the addition rate of the ammonia solution, and the total time of the first contact reaction is 3 h;

[0128] Then, stop adding the first alkali solution so that the pH value of the slurry is reduced to 10.5 (pH value measured based on a liquid temperature of 50°C). After that, in a nitrogen atmosphere (the oxygen content in the reactor is 0.1% by volume), another portion of the first material, the second portion of the first alkali solution and the second portion of the ammonia solution are added simultaneously under the conditions of a stirring power density of 7W / L and a reaction temperature of 60°C to carry out a second contact reaction, wherein the addition rate of the first material is 0.28L / h. In addition, the reaction pH is maintained at 10.5 (pH value measured based on a liquid temperature of 50°C) by adjusting the addition rate of the first alkali solution, and the NH3 concentration is maintained at 6g / L by adjusting the addition rate of the ammonia solution. The total time of the second contact reaction is 180h. When the D50 of the solid particles in the reactor is 8.2μm, the reaction is completed, and the feeding is stopped to obtain the second material.

[0129] When the total volume of the material in the reactor reaches 8L, start the diaphragm pump and the concentrator to concentrate the slurry, the concentrated liquid flows back to the reactor, and the clear liquid is discharged into the waste liquid tank;

[0130] (4) adding the second material into a washing machine, washing with deionized water, a sodium hydroxide solution having a mass fraction of 1 wt % and deionized water in sequence, the total alkali washing time being 2 h, until the pH value of the washing solution is below 8.0 (test value under 25° C. and normal pressure), stopping washing, and obtaining a third material;

[0131] (5) The third material was dried at 120° C. for 3 h. After drying, it was sieved and demagnetized to obtain a nickel-cobalt-manganese-aluminum precursor A1, the parameters of which are listed in Table 1.

[0132] The XRD test of NiCoMnAl precursor A1 was carried out, and the results are as follows Figure 1 As shown, Figure 1 The presence of characteristic peaks of Al(OH)3 and nickel-cobalt-manganese hydroxides indicates that the nickel-cobalt-manganese-aluminum precursor contains a chemical formula of Ni 0.842 Co 0.053 Mn 0.105 (OH)2 and Al(OH)3, and the nickel-cobalt-manganese hydroxide has a β-crystal form, indicating that the nickel-cobalt-manganese-aluminum precursor prepared by the method of the present application has a two-phase microscopic crystal structure.

[0133] The SEM test of NiCoMnAl precursor A1 was carried out, and the results are as follows Figure 3 As shown in the low-magnification electron microscope photo (left), it can be seen that the precursor particles are uniform and there are no small particles, indicating that Al(OH)3 is doped into Ni 0.842 Co 0.053 Mn 0.105(OH)2 precursor; From the high-power electron microscope photo (right), it can be clearly seen that the precursor particles are composed of Ni with a lamellar morphology. 0.842 Co 0.053 Mn 0.105 (OH)2 and Al(OH)3 with granular morphology are intertwined to form spherical secondary particles.

[0134] The particle size distribution test of nickel-cobalt-manganese-aluminum precursor A1 was carried out, and the results are as follows Figure 5 As shown in the figure, it can be seen that the particle size distribution has a high concentration, which can also indicate that Al(OH)3 does not exist in the precursor in the form of a single phase, but is mixed with Ni 0.842 Co 0.053 Mn 0.105 (OH)2 particles.

[0135] Example 2

[0136] The nickel-cobalt-manganese-aluminum precursor A2 was prepared by the following steps:

[0137] (1) Dissolve NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O in deionized water to prepare a mixture containing Ni 2+ 、Co 2+ and Mn 2+ of solution;

[0138] The total concentration of nickel ions, cobalt ions and manganese ions is 2.0 mol / L, among which n(Ni 2+ ):n(Co 2+ ):n(Mn 2+ )=84.2:5.3:10.5 (molar ratio);

[0139] Add Al(OH)3 to deionized water, and grind it at a speed of 2500 r / min for 3 hours to form a suspension containing Al(OH)3 nanoparticles with a solid content of 5 weight %; mix the suspension containing Al(OH)3 nanoparticles with a solution containing a nickel source, a cobalt source and a manganese source to obtain a first material; the first material is always in a stirring state to avoid precipitation of Al(OH)3;

[0140] The D50 of Al(OH)3 nanoparticles in the suspension containing Al(OH)3 is 20 nm;

[0141] The molar ratio of Al(OH)3 to the metal element is 0.05:1.

[0142] Adding sodium hydroxide into deionized water to prepare a first alkaline solution with a concentration of 6 mol / L;

[0143] Add 25% concentrated ammonia water into deionized water to prepare a 22% ammonia solution;

[0144] (2) adding 8 L of deionized water into a 10 L reactor, and adding the first part of the first alkaline solution and the first part of the ammonia solution into the reactor under stirring as a reaction base solution;

[0145] The pH value of the reaction base liquid was 11.5 (pH value measured based on a liquid temperature of 50°C), the concentration of NH3 was 3 g / L, and the stirring power density of the reaction base liquid was 7 W / L;

[0146] (3) In a nitrogen atmosphere (the oxygen content in the reactor is 0.1% by volume), under the conditions of a stirring power density of 9 W / L and a reaction temperature of 65°C, a portion of the first material, a second portion of the first alkali solution, and a second portion of the ammonia solution are added to the reactor in parallel to carry out a first contact reaction, wherein the addition rate of the first material is 0.30 L / h. In addition, the reaction pH is maintained at 11.5 (pH measured based on a liquid temperature of 50°C) by adjusting the addition rate of the first alkali solution, and the NH3 concentration is maintained at 3 g / L by adjusting the addition rate of the ammonia solution, and the total time of the first contact reaction is 1.5 h;

[0147] Then, stop adding the first alkali solution so that the pH value of the slurry is reduced to 10.3 (pH value measured based on a liquid temperature of 50°C). After that, in a nitrogen atmosphere (the oxygen content in the reactor is 0.1% by volume), another part of the first material, the second part of the first alkali solution and the second part of the ammonia solution are added simultaneously under the conditions of a stirring power density of 7W / L and a reaction temperature of 65°C to carry out a second contact reaction, wherein the addition rate of the first material is 0.30L / h. In addition, the reaction pH value is maintained at 10.3 (pH value measured based on a liquid temperature of 50°C) by adjusting the addition rate of the first alkali solution, and the NH3 concentration is maintained at 3g / L by adjusting the addition rate of the ammonia solution. The total time of the second contact reaction is 200h. When the D50 of the solid particles in the reactor is 9.5μm, the reaction is completed, and the feeding is stopped to obtain the second material.

[0148] Start the diaphragm pump and the thickener to concentrate the slurry, the concentrated liquid flows back to the reactor, and the clear liquid is discharged into the waste liquid tank;

[0149] (4) adding the second material into a washing machine, washing with deionized water, a sodium hydroxide solution having a mass fraction of 2 wt % and deionized water in sequence, the total alkali washing time being 1 h, and stopping washing until the pH value of the washing solution is below 8.0 (test value under normal pressure at 25° C.), thereby obtaining a third material;

[0150] (5) The third material was dried at 120° C. for 3 h. After drying, it was sieved and demagnetized to obtain a nickel-cobalt-manganese-aluminum precursor A2, the parameters of which are listed in Table 1.

[0151] The XRD test of the nickel-cobalt-manganese-aluminum precursor A2 was carried out. The XRD spectrum showed the characteristic peaks of Al(OH)3 and nickel-cobalt-manganese hydroxide, indicating that the nickel-cobalt-manganese-aluminum precursor contained a chemical formula of Ni 0.842 Co 0.053 Mn 0.105 (OH)2 and Al(OH)3, and the nickel cobalt manganese hydroxide has a β crystal form; SEM test of precursor A2 shows that it has a two-phase microscopic crystal structure in which Al(OH)3 crystals are dispersed in nickel cobalt manganese hydroxide crystals.

[0152] Example 3

[0153] The nickel-cobalt-manganese-aluminum precursor A3 was prepared by the following steps:

[0154] (1) Dissolve NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O in deionized water to prepare a mixture containing Ni 2+ 、Co 2+ and Mn 2+ of solution;

[0155] The total concentration of nickel ions, cobalt ions and manganese ions is 1.5 mol / L, among which n(Ni 2+ ):n(Co 2+ ):n(Mn 2+ )=84.2:5.3:10.5 (molar ratio);

[0156] Add Al(OH)3 to deionized water, and grind it at a speed of 2500 r / min for 5 hours to form a suspension containing Al(OH)3 nanoparticles with a solid content of 5 weight %; mix the suspension containing Al(OH)3 nanoparticles with a solution containing a nickel source, a cobalt source and a manganese source to obtain a first material; the first material is always in a stirring state to avoid precipitation of Al(OH)3;

[0157] The D50 of Al(OH)3 nanoparticles in the suspension containing Al(OH)3 is 30nm;

[0158] The molar ratio of Al(OH)3 to the metal element is 0.05:1.

[0159] Adding sodium hydroxide into deionized water to prepare a first alkaline solution with a concentration of 4 mol / L;

[0160] Add 25% concentrated ammonia water into deionized water to prepare a 22% ammonia solution;

[0161] (2) adding 8 L of deionized water into a 10 L reactor, and adding the first part of the first alkaline solution and the first part of the ammonia solution into the reactor under stirring as a reaction base solution;

[0162] The pH value of the reaction base liquid was 12.5 (pH value measured based on a liquid temperature of 50°C), the concentration of NH3 was 10 g / L, and the stirring power density of the reaction base liquid was 9 W / L;

[0163] (3) In a nitrogen atmosphere (the oxygen content in the reactor is 0.2% by volume), under the conditions of a stirring power density of 9 W / L and a reaction temperature of 60°C, a portion of the first material, a second portion of the first alkali solution, and a second portion of the ammonia solution are added to the reactor in parallel to carry out a first contact reaction, wherein the addition rate of the first material is 0.40 L / h. In addition, the reaction pH is maintained at 12.5 (pH measured based on a liquid temperature of 50°C) by adjusting the addition rate of the first alkali solution, and the NH3 concentration is maintained at 10 g / L by adjusting the addition rate of the ammonia solution, and the total time of the first contact reaction is 1.0 h;

[0164] Then, stop adding the first alkali solution so that the pH value of the slurry is reduced to 10.3 (pH value measured based on a liquid temperature of 50°C). After that, in a nitrogen atmosphere (the oxygen content in the reactor is 0.2% by volume), another part of the first material, the second part of the first alkali solution and the second part of the ammonia solution are added simultaneously under the conditions of a stirring density power of 7W / L and a reaction temperature of 60°C to carry out a second contact reaction, wherein the addition rate of the first material is 0.30L / h. In addition, the reaction pH value is maintained at 10.3 (pH value measured based on a liquid temperature of 50°C) by adjusting the addition rate of the first alkali solution, and the NH3 concentration is maintained at 10g / L by adjusting the addition rate of the ammonia solution. The total time of the second contact reaction is 200h. When the D50 of the solid particles in the reactor is 9.8μm, the reaction is completed, and the feeding is stopped to obtain the second material.

[0165] Start the diaphragm pump and the thickener to concentrate the slurry, the concentrated liquid flows back to the reactor, and the clear liquid is discharged into the waste liquid tank;

[0166] (4) adding the second material into a washing machine, washing with deionized water, a sodium hydroxide solution having a mass fraction of 1 wt % and deionized water in sequence, the total alkali washing time being 2 h, until the pH value of the washing solution is below 8.0 (test value under 25° C. and normal pressure), stopping washing, and obtaining a third material;

[0167] (5) The third material was dried at 120° C. for 3 h. After drying, it was sieved and demagnetized to obtain a nickel-cobalt-manganese-aluminum precursor A3, the parameters of which are listed in Table 1.

[0168] The XRD test of the nickel-cobalt-manganese-aluminum precursor A3 was carried out. The XRD spectrum showed the characteristic peaks of Al(OH)3 and nickel-cobalt-manganese hydroxide, indicating that the nickel-cobalt-manganese-aluminum precursor contains a chemical formula of Ni 0.842 Co 0.053 Mn 0.105 (OH)2 and Al(OH)3, and the nickel cobalt manganese hydroxide has a β crystal form; SEM test of precursor A3 shows that it has a two-phase microscopic crystal structure in which Al(OH)3 crystals are dispersed in nickel cobalt manganese hydroxide crystals.

[0169] Example 4

[0170] The nickel-cobalt-manganese-aluminum precursor A4 was prepared by the following steps:

[0171] (1) Dissolve NiCl2·6H2O, CoCl2·2H2O, and MnCl2·4H2O in deionized water to prepare a solution containing Ni 2+ 、Co 2+ and Mn 2+ of solution;

[0172] The total concentration of nickel ions, cobalt ions and manganese ions is 2.5 mol / L, among which n(Ni 2+ ):n(Co 2+ ):n(Mn 2+ )=85.6:8.2:6.2 (molar ratio);

[0173] Add Al(OH)3 to deionized water, and grind it at a speed of 3000 r / min for 5 hours to form a suspension containing Al(OH)3 nanoparticles with a solid content of 3 weight %; mix the suspension containing Al(OH)3 nanoparticles with a solution containing a nickel source, a cobalt source and a manganese source to obtain a first material; the first material is always in a stirring state to avoid precipitation of Al(OH)3;

[0174] The D50 of Al(OH)3 nanoparticles in the suspension containing Al(OH)3 is 30nm;

[0175] The molar ratio of Al(OH)3 to the metal element is 0.03:1.

[0176] Adding sodium hydroxide into deionized water to prepare a first alkaline solution with a concentration of 6 mol / L;

[0177] Add 25% concentrated ammonia water into deionized water to prepare a 15% ammonia water solution;

[0178] (2) adding 3 L of deionized water into a 10 L reactor, and adding the first part of the first alkaline solution and the first part of the ammonia solution into the reactor under stirring as a reaction base solution;

[0179] The pH value of the reaction base liquid was 11.5 (pH value measured based on a liquid temperature of 50°C), the concentration of NH3 was 5 g / L, and the stirring power density of the reaction base liquid was 9 W / L;

[0180] (3) In a nitrogen atmosphere (the oxygen content in the reactor is 0.1% by volume), under the conditions of a stirring power density of 9 W / L and a reaction temperature of 50°C, a portion of the first material, a second portion of the first alkali solution, and a second portion of the ammonia solution are added to the reactor in parallel to carry out a first contact reaction, wherein the addition rate of the first material is 0.30 L / h. In addition, the reaction pH is maintained at 11.5 (pH measured based on a liquid temperature of 50°C) by adjusting the addition rate of the first alkali solution, and the NH3 concentration is maintained at 5 g / L by adjusting the addition rate of the ammonia solution, and the total time of the first contact reaction is 1.0 h;

[0181] Then, stop adding the first alkali solution so that the pH value of the slurry is reduced to 10.6 (pH value measured based on a liquid temperature of 50°C). After that, in a nitrogen atmosphere (the oxygen content in the reactor is 0.1% by volume), another portion of the first material, the second portion of the first alkali solution and the second portion of the ammonia solution are added simultaneously under the conditions of a stirring power density of 7W / L and a reaction temperature of 50°C to carry out a second contact reaction, wherein the addition rate of the first material is 0.30L / h. In addition, the reaction pH is maintained at 10.6 (pH value measured based on a liquid temperature of 50°C) by adjusting the addition rate of the first alkali solution, and the NH3 concentration is maintained at 5g / L by adjusting the addition rate of the ammonia solution. The total time of the second contact reaction is 250h. When the D50 of the solid particles in the reactor is 12.1μm, the reaction is completed, and the feeding is stopped to obtain the second material.

[0182] When the total volume of the material in the reactor reaches 8L, start the diaphragm pump and the concentrator to concentrate the slurry, the concentrated liquid flows back to the reactor, and the clear liquid is discharged into the waste liquid tank;

[0183] (4) adding the second material into a washing machine, washing with deionized water, a sodium hydroxide solution having a mass fraction of 1 wt % and deionized water in sequence, the total alkali washing time being 2 h, until the pH value of the washing solution is below 8.0 (test value under 25° C. and normal pressure), stopping washing, and obtaining a third material;

[0184] (5) The third material was dried at 150° C. for 5 h. After drying, it was sieved and demagnetized to obtain a nickel-cobalt-manganese-aluminum precursor A4, the parameters of which are listed in Table 1.

[0185] The XRD test of the nickel-cobalt-manganese-aluminum precursor A4 was carried out. The XRD spectrum showed the characteristic peaks of Al(OH)3 and nickel-cobalt-manganese hydroxide, indicating that the nickel-cobalt-manganese-aluminum precursor contained a chemical formula of Ni 0.856 Co 0.082 Mn 0.062 (OH)2 and Al(OH)3, and the nickel cobalt manganese hydroxide has a β crystal form; SEM test of the nickel cobalt manganese aluminum precursor A4 shows that it has a two-phase microscopic crystal structure in which Al(OH)3 crystals are dispersed in the nickel cobalt manganese hydroxide crystals.

[0186] Example 5

[0187] The nickel-cobalt-manganese-aluminum precursor A5 was prepared by the following steps:

[0188] (1) Dissolve NiCl2·6H2O, CoCl2·2H2O, and MnCl2·4H2O in deionized water to prepare a solution containing Ni 2+ 、Co 2+ and Mn 2+ of solution;

[0189] The total concentration of nickel ions, cobalt ions and manganese ions is 2.1 mol / L, among which n(Ni 2+ ):n(Co 2+ ):n(Mn 2+ )=79.6:15.3:5.1 (molar ratio);

[0190] Add Al(OH)3 to deionized water, and grind it at a speed of 3000 r / min for 2 hours to form a suspension containing Al(OH)3 nanoparticles with a solid content of 2 weight percent; mix the suspension containing Al(OH)3 nanoparticles with a solution containing a nickel source, a cobalt source and a manganese source to obtain a first material; the first material is always in a stirring state to avoid precipitation of Al(OH)3;

[0191] The D50 of Al(OH)3 nanoparticles in the suspension containing Al(OH)3 is 20 nm;

[0192] The molar ratio of Al(OH)3 to the metal element is 0.02:1.

[0193] Adding sodium hydroxide into deionized water to prepare a first alkaline solution with a concentration of 10 mol / L;

[0194] Add 25% concentrated ammonia water into deionized water to prepare a 15% ammonia water solution;

[0195] (2) adding 5 L of deionized water into a 10 L reactor, and adding a portion of the first alkali solution and a portion of the ammonia solution into the reactor under stirring as a reaction base solution;

[0196] The pH value of the reaction base liquid was 11.5 (pH value measured based on a liquid temperature of 50°C), the concentration of NH3 was 10 g / L, and the stirring power density of the reaction base liquid was 9 W / L;

[0197] (3) In a nitrogen atmosphere (the oxygen content in the reactor is 0.1% by volume), under the conditions of a stirring power density of 9 W / L and a reaction temperature of 60°C, a portion of the first material, a second portion of the first alkali solution, and a second portion of the ammonia solution are added to the reactor in parallel to carry out a first contact reaction, wherein the addition rate of the first material is 0.35 L / h. In addition, the reaction pH value is maintained at 11.5 (pH value measured based on a liquid temperature of 50°C) by adjusting the addition rate of the first alkali solution, and the NH3 concentration is maintained at 10 g / L by adjusting the addition rate of the ammonia solution, and the total time of the first contact reaction is 1.0 h;

[0198] Then, stop adding the first alkali solution so that the pH value of the slurry is reduced to 10.0 (pH value measured based on a liquid temperature of 50°C). After that, in a nitrogen atmosphere (the oxygen content in the reactor is 0.1% by volume), another portion of the first material, the second portion of the first alkali solution and the second portion of the ammonia solution are added simultaneously under the conditions of a stirring power density of 7W / L and a reaction temperature of 60°C to carry out a second contact reaction, wherein the addition rate of the first material is 0.35L / h. In addition, the reaction pH is maintained at 10.0 (pH value measured based on a liquid temperature of 50°C) by adjusting the addition rate of the first alkali solution, and the NH3 concentration is maintained at 10g / L by adjusting the addition rate of the ammonia solution. The total time of the second contact reaction is 250h. When the D50 of the solid particles in the reactor is 14.7μm, the reaction is completed, and the feeding is stopped to obtain the second material.

[0199] When the total volume of the material in the reactor reaches 8L, start the diaphragm pump and the concentrator to concentrate the slurry, the concentrated liquid flows back to the reactor, and the clear liquid is discharged into the waste liquid tank;

[0200] (4) adding the second material into a washing machine, washing with deionized water, a sodium hydroxide solution having a mass fraction of 1 wt % and deionized water in sequence, the total alkali washing time being 3 h, until the pH value of the washing solution is below 8.0 (test value under normal pressure at 25° C.), stopping washing, and obtaining a third material;

[0201] (5) The third material was dried at 200° C. for 3 h. After drying, it was sieved and demagnetized to obtain a nickel-cobalt-manganese-aluminum precursor A5, the parameters of which are listed in Table 1.

[0202] The nickel-cobalt-manganese-aluminum precursor A5 was tested by XRD. The XRD spectrum showed the characteristic peaks of Al(OH)3 and nickel-cobalt-manganese hydroxide, indicating that the nickel-cobalt-manganese-aluminum precursor contained a chemical formula of Ni 0.796 Co 0.153 Mn 0.051 (OH)2 and Al(OH)3, and the nickel cobalt manganese hydroxide has a β crystal form; SEM test of the nickel cobalt manganese aluminum precursor A5 showed that it has a two-phase microscopic crystal structure in which Al(OH)3 crystals are dispersed in the nickel cobalt manganese hydroxide crystals.

[0203] Comparative Example 1

[0204] The nickel-cobalt-manganese-aluminum precursor D1 was prepared by the following steps:

[0205] (1) NiSO4·6H2O, CoSO4·7H2O, MnSO4·H2O and Al2(SO4)3·18H2O are dissolved in deionized water to prepare a mixed metal salt solution;

[0206] Ni 2+ 、Co 2+ , Mn 2+ and Al 3+ The total concentration is 2.2 mol / L, of which n(Ni 2+ ):n(Co 2+ ):n(Mn 2+ ):n(Al 3 + )=80:5:10:5 (molar ratio);

[0207] Adding sodium hydroxide into deionized water to prepare a first alkaline solution with a concentration of 5 mol / L;

[0208] Add 25% concentrated ammonia water into deionized water to prepare an 18% ammonia solution;

[0209] (2) adding 5 L of deionized water into a 10 L reactor, and adding the first part of the first alkaline solution and the first part of the ammonia solution into the reactor under stirring as a reaction base solution;

[0210] The pH value of the reaction base liquid is 12.0 (pH value measured based on a liquid temperature of 50°C), the concentration of NH3 is 6 g / L, and the stirring power density of the reaction base liquid is 7 W / L;

[0211] (3) In a nitrogen atmosphere (the oxygen content in the reactor is 0.1% by volume), under the conditions of a stirring power density of 9 W / L and a reaction temperature of 60°C, a portion of the mixed metal salt solution, a second portion of the first alkali solution, and a second portion of the ammonia solution are added to the reactor in parallel to carry out a first contact reaction, wherein the addition rate of the first material is 0.28 L / h. In addition, the reaction pH value is maintained at 12.0 (pH value measured based on a liquid temperature of 50°C) by adjusting the addition rate of the first alkali solution, and the NH3 concentration is maintained at 6 g / L by adjusting the addition rate of the ammonia solution, and the total time of the first contact reaction is 3 h;

[0212] Then, the addition of the first alkaline solution was stopped so that the pH value of the slurry dropped to 10.5 (pH value measured based on a liquid temperature of 50°C). After that, in a nitrogen atmosphere (the oxygen content in the reactor was 0.1% by volume), another part of the mixed metal salt solution, the second part of the first alkaline solution and the second part of the ammonia solution were added simultaneously at a stirring power density of 7W / L and a reaction temperature of 60°C to carry out a second contact reaction, wherein the addition rate of the first material was 0.28L / h. In addition, the reaction pH was maintained at 10.5 (pH value measured based on a liquid temperature of 50°C) by adjusting the addition rate of the first alkaline solution, and the NH3 concentration was maintained at 6g / L by adjusting the addition rate of the ammonia solution. The total time of the second contact reaction was 180h.

[0213] When the total volume of the material in the reactor reaches 8L, start the diaphragm pump and the concentrator to concentrate the slurry, the concentrated liquid flows back to the reactor, and the clear liquid is discharged into the waste liquid tank;

[0214] When the reaction time is the same as step (3) of Example 1, the feeding is stopped to obtain a second material;

[0215] (4) adding the second material into a washing machine, washing with deionized water, a sodium hydroxide solution having a mass fraction of 1 wt % and deionized water in sequence, the total alkali washing time being 2 h, until the pH value of the washing solution is below 8.0 (test value under 25° C. and normal pressure), stopping washing, and obtaining a third material;

[0216] (5) The third material was dried at 120° C. for 10 h. After drying, it was sieved and demagnetized to obtain a nickel-cobalt-manganese-aluminum precursor D1. According to the calculation of the feed, the chemical formula of the nickel-cobalt-manganese-aluminum precursor D1 is Ni 0.8 Co 0.05 Mn 0.1 Al 0.05 (OH) 2.05 , and its parameters are listed in Table 1.

[0217] The XRD test of NiCoMnAl precursor D1 was carried out, and the results are as follows Figure 2 As shown, Figure 2 There are only characteristic peaks of nickel-cobalt-manganese-aluminum hydroxide, but no characteristic peaks of Al(OH)3 and nickel-cobalt-manganese hydroxide, indicating that the nickel-cobalt-manganese-aluminum precursor does not contain nickel-cobalt-manganese hydroxide and Al(OH)3, and does not have a two-phase structure.

[0218] The SEM test of NiCoMnAl precursor D1 was carried out, and the results are as follows Figure 4 shown; from Figure 4 As can be seen in the left figure, the precursor D1 contains a large number of small particles, and the particle distribution is uneven, which is an inherent defect of the traditional co-precipitation method for synthesizing nickel-cobalt-manganese-aluminum hydroxide precursors. Figure 4 As can be seen in the right figure, the spherical particles are stacked by primary particles with a lamellar structure, and the primary particles are not densely packed and have more pores, which is different from the nickel-cobalt-manganese-aluminum hydroxide precursor with a two-phase structure ( Figure 3 The right picture) is quite different.

[0219] Table 1

[0220]

[0221]

[0222] Preparation Examples 1-5

[0223] The nickel-cobalt-manganese-aluminum-lithium quaternary materials A1-1 to A5-1 are prepared by the following steps:

[0224] S1. According to the molar ratio of Li / M=1.05 (M=Ni+Co+Al+Mn), lithium hydroxide monohydrate LiOH·H2O and a nickel-cobalt-manganese-aluminum hydroxide precursor having a two-phase crystal structure are ball-milled for 3 hours to obtain a first product;

[0225] S2. Calcine the first product in an oxygen atmosphere for 15 hours at a calcination temperature of 750° C. to obtain nickel-cobalt-manganese-aluminum-lithium quaternary materials A1-1 to A5-1. The parameters are listed in Table 2.

[0226] Preparation Comparative Example 1

[0227] The nickel-cobalt-manganese-aluminum lithium quaternary material D1-1 was prepared by the method of Preparation Example 1, and the parameters are listed in Table 2. The difference is that the nickel-cobalt-manganese-aluminum precursor D1 prepared in Comparative Example 1 was used as the precursor material.

[0228] Preparation Comparative Example 2

[0229] S1. According to the molar ratio of Li / M=1.05 (M=Ni+Co+Mn+Al), lithium hydroxide monohydrate LiOH·H2O, nickel cobalt manganese hydroxide precursor and aluminum hydroxide are ball-milled and mixed (the feeding ratio is set according to the element ratio in the product) for 3 hours to obtain the first product;

[0230] S2. The first product was calcined in an oxygen atmosphere for 15 hours to obtain a nickel-cobalt-manganese-aluminum lithium quaternary material D2-1, wherein the calcination temperature was 750° C. The material was tested for its physicochemical properties and electrochemical properties, and the test results are listed in Table 2.

[0231] XRD tests were performed on the prepared nickel-cobalt-manganese-aluminum lithium quaternary materials A1-1, D1-1, and D2-1, and the results are as follows: Figure 6 As shown in the figure, it can be seen that the XRD curves of A1-1 and D1-1 are Li 1.05 Ni 0.8 Co 0.05 Mn 0.1 Al 0.05 O2 has a single-phase structure and does not contain impurity peaks. In the XRD curve of the D2-1 sample, there are diffraction peaks at 22.962° and 33.089°, indicating the presence of β-LiAlO2 phase, indicating that the Al element can be dispersed into the crystal structure to form a single crystal structure phase in the nickel-cobalt-manganese-aluminum lithium quaternary material prepared by the nickel-cobalt-manganese-aluminum precursor prepared by the method disclosed in the present invention.

[0232] Test Case

[0233] The steps of preparing a lithium ion battery using the nickel-cobalt-manganese-aluminum-lithium quaternary material of the above-mentioned preparation example and the preparation comparative example are as follows:

[0234] Accurately weigh the positive electrode materials A1-1 to A5-1, D1-1 and D2-1, the conductive agent and PVDF in a mass ratio of 8:1:1, add the three materials to NMP, and stir to make a slurry. Spread the stirred slurry on a 16μm thick aluminum foil and dry it at 110℃ for 30min. Roll the dried electrode sheet and punch it into an electrode sheet with a diameter of φ12 with a punching machine. Dry the electrode sheet in a vacuum oven at 120℃ for 12h. The surface density of the electrode sheet is about 100g / m 2 .

[0235] In a glove box with argon atmosphere, a Li sheet was used as the negative electrode, the electrode sheet prepared above was used as the positive electrode, a 1 mol / L LiPF6 EC / EMC / DMC solution was used as the electrolyte, and a PP / PE polymer separator was used to assemble a CR2032 button half-cell.

[0236] The prepared battery was subjected to electrical performance tests, and the results are listed in Table 2. The test conditions include: discharge capacity test conditions: charge and discharge voltage is 2.75-4.3V, charge and discharge rate is 0.1C, and test temperature is 25°C; during the cycle performance test, the charge and discharge rate is 0.5C.

[0237] Table 2

[0238]

[0239]

[0240] According to the data in Tables 1 and 2, the nickel-cobalt-manganese-aluminum precursor prepared by the method disclosed in the present invention has a higher tap density, a larger particle size and a smaller specific surface area, and the nickel-cobalt-manganese-aluminum lithium oxide quaternary material prepared therefrom has a larger tap density and particle size, and has better electrochemical properties.

[0241] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0242] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0243] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A nickel-cobalt-manganese-aluminum precursor having a two-phase structure, characterized in that: The nickel-cobalt-manganese-aluminum precursor includes secondary particles containing nickel-cobalt-manganese hydroxide and Al(OH) 3.

2. The nickel-cobalt-manganese-aluminum precursor according to claim 1, wherein The nickel-cobalt-manganese hydroxide has a β crystal form; The chemical formula of the nickel-cobalt-manganese hydroxide is Ni 1-x-y Co x Mn y (OH)2, 0.05≤x≤0.15, 0.05≤y≤0.

15.

3. The nickel-cobalt-manganese-aluminum precursor according to claim 1, wherein In the XRD spectrum of the nickel-cobalt-manganese-aluminum precursor, there are characteristic peaks of Al(OH)3 crystals and characteristic peaks of nickel-cobalt-manganese hydroxide crystals.

4. The nickel-cobalt-manganese-aluminum precursor according to claim 1, wherein The secondary particles have a two-phase microscopic crystal structure in which Al(OH) 3 crystals are dispersed in nickel-cobalt-manganese hydroxide crystals.

5. The nickel-cobalt-manganese-aluminum precursor according to claim 1, wherein The tap density of the secondary particles is 2.0 g / cm 3 Above, the specific surface area is 10-15m 2 / g, D50 is 8-15μm.

6. The nickel-cobalt-manganese-aluminum precursor according to claim 1, wherein: In the nickel-cobalt-manganese-aluminum precursor, the molar ratio of aluminum element to metal element is (0.02-0.05):

1.

7. A method for preparing a nickel-cobalt-manganese-aluminum precursor having a two-phase structure, characterized in that: The method comprises: under stirring conditions, subjecting a first material containing a nickel source, a cobalt source, a manganese source and Al(OH)3 nanoparticles, a first alkaline solution and an ammonia solution to a first contact reaction and a second contact reaction, wherein the first contact reaction and the second contact reaction are carried out in an inert atmosphere; The D50 of the Al(OH)3 nanoparticles is 10-50nm; The first contact reaction is carried out under the condition that the pH value measured at a liquid temperature of 50° C. is 11.5-12.5; The second contact reaction is carried out under the condition that the pH value measured at a liquid temperature of 50° C. is 10.0-10.

6.

8. The method according to claim 7, wherein: The method for preparing the first material comprises: mixing a suspension containing the Al(OH)3 nanoparticles with a solution containing the nickel source, the cobalt source and the manganese source under stirring; Optionally, the solid content of the suspension is 10-30% by weight; Optionally, the total concentration of cobalt ions, nickel ions and manganese ions in the solution is 1.5-2.5 mol / L; Optionally, in the first material, the molar ratio of aluminum element to metal element is (0.02-0.05):

1.

9. The method according to claim 7, wherein: The nickel source includes nickel sulfate and / or nickel chloride; The cobalt source includes cobalt sulfate and / or cobalt chloride; The manganese source includes manganese sulfate and / or manganese chloride.

10. The method according to claim 7, wherein: The first alkaline solution contains sodium hydroxide and / or potassium hydroxide; The concentration of the first alkaline solution is 4-10 mol / L, and the mass fraction of the ammonia solution is 15-22%.

11. The method according to claim 7, wherein: The method comprises the following steps: a. Add water, the first part of the first alkaline solution and the first part of the ammonia solution into a reaction kettle under stirring; The total volume of the water, the first alkaline solution of the first part and the ammonia solution of the first part accounts for 30-80% of the volume fraction of the reactor; b. adding a portion of the first material, a second portion of the first alkali solution and a second portion of the ammonia solution into the reactor of step a under stirring to carry out the first contact reaction; c. Under stirring conditions, adding another portion of the first material, a third portion of the first alkali solution and a third portion of the ammonia solution to the reactor in step b to carry out the second contact reaction, and stopping feeding when the D50 of the solid material in the reactor is 8-15 μm; The first contact reaction time is 1-3 hours, and the second contact reaction time is 180-250 hours; When the volume of the material in the reactor accounts for 80%-85% of the total volume of the reactor, the clear liquid is discharged from the reactor through a concentrator; The inert atmosphere includes nitrogen atmosphere and / or argon atmosphere; In step b and step c, the oxygen content in the reaction kettle is below 0.2 volume %.

12. The method according to claim 11, wherein: In step a, in the solution in the reactor, the concentration of NH3 is 3-10 g / L, the pH value of the solution in the reactor is 11.5-12.5 measured at a liquid temperature of 50° C., and the stirring power density of the solution is 7-9 W / L; In step b and step c, the concentration of NH3 in the slurry in the reactor is 3-10 g / L, and the stirring power density of the slurry is 7-9 W / L; The temperatures of the first contact reaction and the second contact reaction are 50-65° C., respectively.

13. The method according to claim 7, wherein: The method further includes: performing alkaline washing on the second material obtained by the second contact reaction, wherein the alkaline washing includes: washing the second material with water, a second alkaline solution and water in sequence until the pH value of the washing solution is below 8.0; The second alkaline solution contains sodium hydroxide and / or potassium hydroxide, the concentration of the second alkaline solution is 1-2% by weight, and the alkaline washing time is 1-3 hours; Optionally, the method further comprises: drying the third material obtained by the alkali washing, and the conditions of the drying treatment include: time of 3-8 hours and temperature of 120-200°C.

14. A nickel-cobalt-manganese-aluminum precursor having a two-phase structure prepared by the method according to any one of claims 7 to 13.

15. A method for preparing a nickel-cobalt-manganese-aluminum lithium quaternary material, characterized in that: The method includes: The nickel-cobalt-manganese-aluminum precursor according to any one of claims 1 to 6 and 14 is mixed with a lithium source and then heat-treated in an oxygen-containing atmosphere.

16. The method according to claim 15, wherein: The lithium source includes one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium oxalate and lithium nitrate; The molar ratio of the lithium source calculated as lithium element to the nickel-cobalt-manganese-aluminum precursor calculated as metal element is (1.03-1.06):1; Optionally, the mixing method is solid phase ball milling, and the solid phase ball milling time is 1-5 hours.

17. The method according to claim 15, wherein: The heat treatment conditions include: time of 8-20 hours and temperature of 700-950°C.

18. A nickel-cobalt-manganese-aluminum lithium quaternary material prepared by the method according to any one of claims 15 to 17.

19. The nickel-cobalt-manganese-aluminum-lithium quaternary material according to claim 18, wherein: The tap density of the nickel-cobalt-manganese-aluminum lithium quaternary material is 2.3 g / cm 3 Above, D50 is 8-15μm.

20. A lithium ion battery, comprising a positive electrode, an electrolyte and a negative electrode, characterized in that: The positive electrode comprises the nickel-cobalt-manganese-aluminum lithium quaternary material as described in claim 18 or 19.

Citation Information

Patent Citations

  • Aluminum-doped nickel-cobalt-manganese ternary positive electrode material precursor, preparation method and application thereof

    CN112751017A